AN ANALYSIS OF PHILOSOPICAL VALUES OF STOICISM AND IKIGAI AS REFLECTED IN ONE PIECE ANIME - Adryo Alfinandus Sagala; Orestis Soidi; Sandra Rakian (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
This study aims at analyzing the philosophical values of stoicism and Ikigai shown in the One Piece anime. This study focuses its analysis on the character development of the characters in the One Piece anime, specifically on the characters of Monkey D. Luffy and Rorona Zoro. This study is a qualitative descriptive study in which the data collection is carried out through note taking. Note taking in this study is the process in which the researchers watch the anime One Piece several times and take notes on the dialogues and action showing the philosophical values of stoicism and Ikigai. The obtained data are then analyzed by using the content analysis technique. The results show that the values of stoicism give characters peace of mind in the midst of difficult situations and the ability to accept fate. Characters with these values tend to have perseverance, integrity, and a strong moral attitude. Meanwhile, Ikigai values are reflected on the passion for life, satisfaction in making contributions, and the search for a balance between values and skills. These characters tend to have a strong sense of purpose, empathy, and a desire to help others. The values of Stoicism Philosophy and Ikigai Philosophy have an important role in the formation of fictional characters. These two values provide depth, complexity, and strong motivation to characters. The combination of these values creates characters who can face challenges with peace of mind, live according to moral principles, pursue their passions, make contributions, and integrate values with their skills.